Performance of wine bag-in-box during storage: loss of oxygen barrier - Fradique, S. (2012)
Bag-in-box system is a convenient packaging system for wine. Its barrier to oxygen relies, in many cases, in an aluminium metallized polyester film laminated between two polyethylene (PE) layers as the inner bag. One on the most frequently observed system failures is the ingress of wine into the gap between the layers of the double bag. This study aimed at verifying if that influences the barrier of the system to oxygen. The results showed that the contact of wine with this barrier layer, although through a PE layer, promotes the demetallization and consequent loss of barrier properties. The type of wine, in particular its volatile acidity, and the temperatures were two variables assessed. Results showed that wine with higher acidity and stored at higher temperatures tend to yield a higher increase in oxygen transmission rate of the film.